A comparison between cognitive and affective job insecurities. Issue 6 (17th August 2020) - Salas-Nicás, Sergio; Navarro, Albert; Llorens, Clara; Moncada, Salvador
Abstract: Background: Cognitive and affective job insecurity are compared in six aspects related to employment: job loss, worsening of tasks, schedule, salary and workplace, and difficulties over finding an alternative job (also known as labor market insecurity). Methods : Cross-sectional study. Data comes from the third Spanish Psychosocial Risks Survey (2016) which is a representative sample of the Spanish salaried population. Results : Affective responses are more variable than cognitive ones resulting in a low degree of answer concordance (IC95% Kappa = 0.08–0.13 to 0.18–0.23). There is a significant percentage of workers (22.5–50.3%) highly concerned about their future despite perceiving low probabilities of experiencing the specific insecurity threat, except for the labor market insecurity question. Conclusion : The differences observed in the degree of insecurity between the affective and the cognitive forms confirm that they are measuring different components of the insecurity construct. These differences are partly due to the economic situation of their households.